The teaching of English vocabulary through pictorial reading texts and games to a group of primary school students in East Jakarta - Anna Marietta da Silva (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
This community service is a free English tutorial for a group of primary schools’ students aged ten years old residing in Duren Sawit, East Jakarta and its surroundings. The program is part of a bigger tutorial program called Bimbingan Belajar Mita (Bimbel Mita) conducted by a non-profit organization that was initiated by the Maria Clarist congregation sisters around eight years ago. The participants of the six-month program were ten students. The method of the community service was teaching the basic English vocabulary through pictorial short English texts and vocabulary games. The former technique was used for the first half of the semester and the latter for the second half of the period. During the tutorial, the students have acquired a number of the targeted English nouns related to objects in the house, garden, animals, colors, professions, fruits, vegetables; verbs related to daily activities at home and adjectives related to descriptions of objects and human beings and some adverbs. In learning the English vocabulary, they show more enthusiasm for games rather than the pictorial reading texts.